Basal cell carcinoma arising in a sebaceous naevus - Amin, Kavit (J Surg Case Rep, 2015)
Sebaceous naevus is a rare non-melanocytic congenital skin hamartoma. Even more rare is the transformation of these lesions into malignant skin cancers, most notably basal cell carcinomas (BCCs). We discuss a case in an adult with later malignant transformation into BCC reported by clinical pathologists. There is dispute about the accurate incidence of malignant transformation. More recently, research has shown that transformation into BCC is unlikely, in that the origins of these lesions arise in trichoblastoma. Evidence from this comes from the changes in mutation pathways that are distinctly separate. A consensus between dermatology, plastic surgery and clinical pathologists is beneficial to decide the best management for these individuals. The limiting factor is the agreement of diagnosis, compounded with conflicting large series multi-centre trials to determine the likelihood of transformation. We feel that each case should be managed individually taking into account patient and/or parent preference with the surgeon offering advice to help the patient guide management decisions. Patient/parent education is important and long-term follow-up by plastic surgeons or dermatologists is highly recommended.